ANALISIS BENTUK DAN MAKNA PERHITUNGAN WETON PADA TRADISI PERNIKAHAN ADAT JAWA MAYARAKAT DESA NGINGIT TUMPANG (KAJIAN ANTROPOLINGUISTIK) - Simamora, Andika; Ruwaida, Ishma Mahliya; Makarima, Nur Ifa Tamlika; Raharja, Bima Putra Lucky; Risma, Nadia Aviana; Saputro, Rizal Dwi; Ardhian, Dany (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2022)
This research was conducted to determine the form, meaning, and function of wetoncalculation in marriage. Then to find out the weton naming system, the socio-culturalperception of the community towards the weton tradition in marriage. The primary data inthis study is the text that is sensed, such as the names of the wetons themselves, to beanalyzed linguistically and culturally. While the secondary data in this study were obtainedfrom interviews with sources and literature studies from previous studies. Sources of data areinformants, namely Mr. Siswantoro as a pranoto actor and inventor of manten in NgingitVillage, Tumpang District, Malang Regency, and related literature. The data collectiontechnique used is the interview and documentation method. Meanwhile, to analyze the data,this study uses the referential equivalent method. This study obtained the results that there is alexical meaning in the form of weton itself, there are functions and uses of weton to calculatethe compatibility of partners, avoid taboo days and chase good days to get lucky. Until now,the Tumpang people still practice these values because they preserve the cultural heritage oftheir ancestors. The Tumpang community is able to separate cultural affairs from religiousmatters, so that the two can synergize according to their portions.